Monoclonal antibody therapy for COVID-19 during pregnancy - Diana I. Abdulganieva; Ekaterina V. Dyakova; Era V. Ivanova; Nailya G. Shamsutdinova; Asiya R. Yangurazova; Nigina A. Nigmatullina; Ildar F. Fatkullin (ZAO "Consilium Medicum", 2023)
Aim. Pregnancy worsens COVID-19 and has been listed by the US Food and Drug Administration as a high risk factor for complicating COVID-19. The severe course of a new coronavirus infection in some pregnant patients has created the prerequisites for the search for treatment methods that can reduce the likelihood of adverse outcomes. One of these therapy options is treatment with virus-neutralizing antibodies monoclonal antibodies. Experience with the use of monoclonal antibodies for the treatment of pregnant women is very limited, but in 2021 pregnancy was recognized as a high risk factor for the course of a new coronavirus infection, making it possible to use this group of drugs. Materials and methods. We described the experience of COVID-19 monoclonal antibody therapy during pregnancy in the Republic of Tatarstan. A retrospective analysis of 18 case histories of pregnant patients with mild and moderate course of confirmed coronavirus infection, treated with monoclonal antibodies (casirivimab/imdevimab) from March 2022 to June 2022, was carried out on the basis of the Perinatal Center of the Republican Clinical Hospital, Kazan, Republic of Tatarstan. Results. All patients tolerated the administration of casirivimab/imdevimab satisfactorily; no adverse drug reactions were identified. Subjective improvement was observed on the 3rd day of MCA treatment. Delivery through the natural birth canal was carried out on time in 11 women; by caesarean section on time in 5 patients. A follow-up study of children born to 18 patients who had COVID-19 was collected. The age of the children at the time of information collection ranged from 10 months 1 year 1 month. Currently, all children are healthy and developing according to their age. Conclusion. In all pregnant patients with a new coronavirus infection with mild to moderate course, the administration of casirivimab/imdevimab was an effective method of treating the new coronavirus infection. The follow-up of children born from 18 patients was followed: the childrens condition was satisfactory, their development corresponded to their age.